Parasite virulence factors during falciparum malaria: rosetting, cytoadherence, and modulation of cytoadherence by cytokines. - Ringwald, P (1993)
To determine virulence factors of isolates of Plasmodium falciparum and the potential role of cytokines in cerebral malaria, 46 Malagasy patients presenting with cerebral (n = 10), severe (n = 10), and uncomplicated (n = 26) malaria were enrolled in a study. The capacity of 21 of 46 P. falciparum isolates to form rosettes in vitro and to adhere to human umbilical vein endothelial cells (HUVECs) that express intercellular adhesion molecule-1 receptors and to C32 amelanotic melanoma cells that express mainly CD36 receptors was investigated together with the effects of tumor necrosis factor alpha (TNF-alpha), granulocyte macrophage-colony-stimulating factor (GM-CSF), interleukin-3 (IL-3), and IL-6 alone and in two-by-two combinations on the cytoadherence of infected erythrocytes to HUVECs. Plasma levels of these cytokines were also measured in the patients at admission. The percentage of rosette formation was higher for the isolates from patients with cerebral (n = 6; 19.5%) and severe (n = 6; 30.5%) malaria than for those from patients with uncomplicated malaria (n = 9; 5%) (P < 0.002). The cytoadherence properties of the isolates did not differ among the three groups whatever the target cell used, but adherence to melanoma cells was systematically higher than that to HUVECs. Adhesion to HUVECs was increased more after TNF-alpha stimulation than after GM-CSF, IL-3, or IL-6 stimulation (P < 0.01). Only the combination of TNF-alpha and IL-3 enhanced cytoadherence more than TNF-alpha used alone (P < 0.02). No difference in the modulation of cytoadherence by cytokines was found in relation to the severity of the disease. TNF-alpha and IL-6 levels in peripheral blood were higher in the patients with cerebral and severe malaria than in the patients with uncomplicated malaria (P < 0.005). Most of the patients' sera contained little or no IL-3 or GM-CSF. Our results challenge the role of intercellular adhesion molecule-1 as the principal receptor mediating the cytoadherence of P. falciparum-infected erythrocytes and contrast with data obtained in the murine model.